Thermal degradation kinetics of polyesters containing mesogenic aromatic diols - Mule, Smita Atmaram; Ghadage, R. S.; Jacob, Nalini E.; Rajan, C. R.; Ponrathnam, Surendra (Journal Applied Polymer Science, 2005)
A series of polyesters were synthesized by reacting structurally differing aromatic diols with either saturated (flexible) or unsaturated (rigid) dicarboxylic acid halide by a stirred interfacial polycondensation technique. Thermal degradation kinetics of these polyesters were investigated by applying Coats-Redfern and Horowitz-Metzger nonisothermal procedures. The dynamic thermogravimetry experiments were conducted in nitrogen to obtain differential thermogravimetric plots. Thermal stability of these polyesters was discussed on the basis of semiquantitative methods such as differential procedural decomposition temperature, integral procedural decomposition temperature, and fraction decomposition temperature (e.g., 10 % DT). Degradation proceeded in multiple stages. The thermal degradation patterns and activation energies in these stages were discussed in relation to central bridging moieties of aromatic diol. The activation energies of these polyesters were found to be in the range of 100 to 200 kJ/mol. The effect of spacer type on activation energy was also reported. (c) 2005 Wiley Periodicals, Inc.
Keywords: Activation energy; Degradation; kinetics (polym.); Polycondensation; polyesters

Thermotropic behavior of lithocholic acid derivative linked hydroxyethyl cellulose - Shaikh, V. A. E.; Maldar, Noormahamad N.; Lonikar, Shrikant Vitthal; Rajan, C. R.; Ponrathnam, S. (Journal of Applied Polymer Science, 2006)
Various mesogenic lithocholic acid (LA) derivatives [3-acetyl LA (LAAC); 3-propionyl LA (LAP), 3-cinnamoyl LA (LACin); 3-benzoyl LA (LAB), 3-(4-nitrobenzoyl) LA (LANB); and methyl-3-(3-carboxypropionyl) LA, i.e., LA methyl ester monosuccinate (LAMeMS)] were reacted with hydroxyethyl cellulose (HEC) to obtain a series of LA derivatives of HEC. These polymers were characterized by the mesogen content, 1.1, differential scanning calorimetry, and hot-stage coupled polarizing optical microscopy. The degree Of Substitution (DS) ranged from 0.27 to 1.11. Polymers HEC-LAB (DS = 1.11), HEC-LANB (DS = 0.80), HEC-LACin (DS = 0.76), and HEC-LAP (DS = 0.27) exhibited a mesophase on heating whereas HEC-LAB also showed a mesophase on cooling. The other polymers HEC-LAAC (DS = 0.89) and HEC-LAMeMS (DS = 0.36) did not reveal mesophase formation with either heating or cooling. It is observed that the formation of a mesophase is affected by the type of mesogen that is used rather than the mesogen content of the polymer. (c) 2006 Wiley Periodicals, Inc.
Keywords: hydroxyethyl cellulose; lithocholic acid; thermotropic